80.9k views
2 votes
Balance each of the following equations according to the half- reaction method:

(a) Sn2+ + Cu2+ --> Sn4+ + Cu+
(b) H2S + Hg2 2+ --> Hg + S (in acid)
(c) CN- + ClO2 --> CNO- + Cl- (in acid)
(d) Fe2+ + Ce 4+ --> Fe3+ +Ce3+
(e) HBrO --> Br- + O2 (in acid)

1 Answer

1 vote

Answer : The balanced chemical equation in a acidic solution are,

(a)
Sn^(2+)+2Cu^(2+)\rightarrow Sn^(4+)+2Cu^+

(b)
H_2S+Hg_2^(2+)\rightarrow 2Hg+S+2H^+

(c)
5CN^-+2ClO_2+H_2O\rightarrow 5CNO^-+2Cl^-+2H^+

(d)
Fe^(2+)+Ce^(4+)\rightarrow Fe^(3+)+Ce^(3+)

(e)
2HBrO\rightarrow 3Br^-+2Br+2O_2+H_2O+3H^+

Explanation :

Redox reaction or Oxidation-reduction reaction : It is defined as the reaction in which the oxidation and reduction reaction takes place simultaneously.

Oxidation reaction : It is defined as the reaction in which a substance looses its electrons. In this, oxidation state of an element increases. Or we can say that in oxidation, the loss of electrons takes place.

Reduction reaction : It is defined as the reaction in which a substance gains electrons. In this, oxidation state of an element decreases. Or we can say that in reduction, the gain of electrons takes place.

(a) The given chemical reaction is,


Sn^(2+)+Cu^(2+)\rightarrow Sn^(4+)+Cu^+

The oxidation-reduction half reaction will be :

Oxidation :
Sn^(2+)\rightarrow Sn^(4+)+2e^-

Reduction :
Cu^(2+)+1e^-\rightarrow Cu^+

In order to balance the electrons, we multiply the reduction reaction by 2 and then added both equation, we get the balanced redox reaction.

The balanced chemical equation will be,


Sn^(2+)+2Cu^(2+)\rightarrow Sn^(4+)+2Cu^+

(b) The given chemical reaction is,


H_2S+Hg_2^(2+)\rightarrow Hg+S

The oxidation-reduction half reaction will be :

Oxidation :
H_2S\rightarrow S+2H^++2e^-

Reduction :
Hg_2^(2+)+2e^-\rightarrow 2Hg

The electrons in oxidation and reduction reaction are same. Now add both the equation, we get the balanced redox reaction.

The balanced chemical equation in a acidic solution will be,


H_2S+Hg_2^(2+)\rightarrow 2Hg+S+2H^+

(c) The given chemical reaction is,


CN^-+ClO_2\rightarrow CNO^-+Cl^-

The oxidation-reduction half reaction will be :

Oxidation :
CN^-+H_2O\rightarrow CNO^-+2H^++2e^-

Reduction :
ClO_2+4H^++5e^-\rightarrow Cl^-+2H_2O

In order to balance the electrons, we multiply the oxidation reaction by 5 and reduction reaction by 2 and then added both equation, we get the balanced redox reaction.

The balanced chemical equation in a acidic solution will be,


5CN^-+2ClO_2+H_2O\rightarrow 5CNO^-+2Cl^-+2H^+

(d) The given chemical reaction is,


Fe^(2+)+Ce^(4+)\rightarrow Fe^(3+)+Ce^(3+)

The oxidation-reduction half reaction will be :

Oxidation :
Fe^(2+)\rightarrow Fe^(3+)+1e^-

Reduction :
Ce^(4+)+1e^-\rightarrow Ce^(3+)

The electrons in oxidation and reduction reaction are same. Now add both the equation, we get the balanced redox reaction.

The balanced chemical equation will be,


Fe^(2+)+Ce^(4+)\rightarrow Fe^(3+)+Ce^(3+)

(e) The given chemical reaction is,


HBrO\rightarrow Br^-+O_2

The oxidation-reduction half reaction will be :

Oxidation :
HBrO+H_2O\rightarrow O_2+Br+3H^++3e^-

Reduction :
HBrO+H^++2e^-\rightarrow Br^-+H_2O

In order to balance the electrons, we multiply the oxidation reaction by 2 and reduction reaction by 3 and then added both equation, we get the balanced redox reaction.

The balanced chemical equation in a acidic solution will be,


2HBrO\rightarrow 3Br^-+2Br+2O_2+H_2O+3H^+

User Juhanic
by
4.8k points